A INFLUÊNCIA DA PANDEMIA COVID-19 NO COMPORTAMENTO DE COMPRA ONLINE DOS JOVENS ADULTOS - Magalhães, Diana; Oliveira, Luciana; Rodrigues, Maria Antónia (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2023)
This study aims to characterize the changes in online purchasing behaviour, resulting from the COVID-19 pandemic, and to assess the intention to maintain or break with behaviors acquired by young adults. A quantitative methodology was used, supported by an online questionnaire, with a sample of 355 answers. The results reveal an intensification of online shopping, changes in the catalogue of products purchased, and an increase in spending. Trust has no particular influence on the buying behavior analysed, but it is a determining factor in the decision to maintain or break with the behaviors acquired. From a theoretical perspective, this study presents an integrated model for analysing buying behavior in the pandemic context. For management, the results of this study provide information about the behavior during and post-pandemic of the young adult segment. This segment is highlighted for its large adherence to e-commerce and for being the generation of buyers of the future.